The Influence of Attachment to Mother on the Psychological Health of Pre-school Children - Kuftyak, E; Kuklina, K (KnE Life Sciences, 2018)
The research of 97 children (49.5% girls) deals with the contribution of attachment to the mental health of senior pre-school age subjects. Child’s attachment has been assessed by means of the Types of Attachment to Mother Assessment Questionnaire; child’s health has been assessed by comprehensive health evaluation (with defining a health group), R. Sear’s technique, Psychological Health Assessment List and The Strengths and Difficulties Questionnaire. The ratio of pre-school children with secure and insecure attachment constituted 62.9 and 37.1%. Children with secure attachment had basic trust to mother and assurance in her support and acceptance. The obtained results confirmed the known data of the peculiarities of children with insecure attachment. Children with insecure attachment had a higher level of anxiety and a higher level of emotional symptom manifestations and external problems. The obtained multiple regression equation forecasted anxiety, emotional symptoms, hyperactivity and problems with peers according to the indices of attachment (emotional proximity with mother, mother’s empathy and perceiving mother as a source of assistance and support). Mother’s empathy to a child was the most significant for the development of anxiety, hyperactive behavior and pro-social behavior. The obtained results may be used in the preventive and correctional work on keeping and strengthening pre-school children’s mental health. Keywords: attachment to mother, mental health, preschoolers